Comparison of various methods for estimating wave incident angles in the nearshore zone - Ngusaru, AS (Tanzania Journal of Science, 2021)
Five different methods were examined for their suitability in estimating the inshore wave incident angles on a nearshore zone with a complex topography. Visual observation provided preliminary estimates. Two frequency independent methods and one frequency dependent method based on current meter measurements were examined. Another frequency dependent method based on collocated bottom pressure and current meter measurements was also examined. The results from all the methods provided a reasonably consistent estimate of the inshore wave incident angles. The frequency independent methods gave exactly the same results while the frequency dependent methods had a 5% relative error among themselves. Between frequency independent and frequency dependent methods, the relative error was 11%. However, since the frequency dependent methods involve smoothing of the velocity spectra, this method was found to be rather subjective. The frequency independent method based on high passed velocity vectors seems to be easy to apply and to provide unambiguous estimate of inshore wave incident angles.